Management of Ptosis in Kearns–Sayre Syndrome: A Case Report and Literature Review - Moustaine, Moulay O.; Azemour, Zakaria; Mohammed, Frarchi; Benlanda, Othman; Nassik, Hicham; Karkouri, Mehdi (Archives of Plastic Surgery, 2024)
Kearns–Sayre syndrome (KSS) is a rare mitochondrial disease that affects young adults, due to a deletion of mitochondrial DNA and characterized by the triad: age of onset lower than 20 years, chronic progressive external ophthalmoplegia, and an atypical pigmentary retinopathy. It is also characterized by other endocrine, neurological, and especially cardiac impairment with a very high risk of cardiac complications during surgical procedures under all types of anesthesia.We report a case of KSS revealed by severe bilateral ptosis and confirmed by a muscle biopsy with “ragged red fibers.” The ptosis was surgically managed by cautious Frontal suspension under local anesthesia “Frontal nerve block.” Through this case, we discuss challenges in the management of KSS patients.
Keywords: Kearns–Sayre syndrome; ptosis; chronic progressive external ophthalmoplegia; Frontal suspension